Atypical presentation of aortic dissection secondary to a gunshot wound. Issue 6 (19th May 2006) - Domingo, E; Levy, D; Iosovich, S
Abstract : We present a case of aortic dissection secondary to a gunshot wound. The traumatic aortic dissection in this patient occurred secondary to the cavitary forces produced by the bullet passing through the patient's chest. This is a rare phenomenon that could easily be missed if attention is placed only on the more obvious injuries.